Media and the 2014 presidential election: a relationship aided by the political situation (2019)
This article presents a research on the information structure of the media with the highest audience rating in Colombia during the 2014 presidential election in Colombia. This process is widely recognized because the election campaign revolved around the peace process and had the highest abstentionism in recent years (60%), only surpassed by the 1994 presidential election. The process is analyzed from March 15 (after the legislative elections) to June 15, in order to consider both the first and second rounds, as well as the relationship with the results obtained during this electoral process. Therefore, the research was carried out with the critical discourse analysis (CDA) approach, based on the contributions of discourse analysis in terms of its structural description, but with a more stressed interest in social problems in which the abuse of power is practiced, reproduced and scarcely refuted by texts and political discourse. Considering that CDA uses empirical and practical methods for evaluating different discourses, the research takes the concepts developed by theoreticians such as Teun Van Dijk, Gilles Gauthier, Beaudoux, D’Adamo and Slavinsky, as well as the contributions of the agenda setting theory, as key referents, because that ensures the influence of the media on the public in determining and classifying the issues that have media interest. Therefore, a matrix with qualitativequantitative variables of communicational nature was designed, aimed at analyzing whether the news’ structure issued by the selected media spawned a particular political climate, and caused that candidates whose news were more in line with the climate of opinion receive more mentions and be legitimized before the population, compared to the candidates who campaigned based on issues not related to the media agenda, which ends up undermining the democracy of a fair competition between candidates, and the right of the audience to receive impartial information that allows an analysis of the proposals of all candidates without it having been previously distorted.